Surge of the Innovative Quest in the first lockdown period due to the Pandemic Effect - Ghosh, Ishita (Discoveries in Agriculture and Food Sciences, 2021)
When the entire world is reeling under the COVID 19 pandemic effect and the tensed human race is struggling to return back to the normalcy of life, the one thing which has become very active is the grey cells of our brain. The pandemic effect has cut down our physical limits due to the movement constraints. But it is thankfully unable to restrict the ticking of the grey cells of the human brain. As is said, “Necessity is the mother of the invention”. Sure enough!! We can be extremely pleased to know that the innovative surge in science and technology continues unabated in this lockdown period. The prime requirement of the pandemic effect is social distancing, less physical contact and keeping ourselves away from infection by corona virus. Keeping this necessity in mind, the doctors, the engineers, the researchers as well as the students’ community are keeping themselves busy in pumping out the solutions to the currently faced problems. The outputs include automatic masks machines, low cost PPE’s, automatic wash basins, suitable ventilators, sanitizer tunnels etc. This review paper looks into the innovative surge already made and what more can be churned out for the effective social safety in this tensed pandemic effect. The most awaited news as of now is the successful implementation of an effective vaccine and cost effective drugs which can help the human beings breathe easy. The pandemic effect has also showed us the way for a cleaner and greener nature. It is now a challenge to the intellectual world to come up with inexpensive, innovative and smart solutions which will make our beautiful planet safer, greener, cleaner and worthier to live in.